2019
DOI: 10.5152/tjar.2019.82258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcranial Doppler Ultrasonography in the Diagnosis of Brain Death

Abstract: the manuscript, references should be cited using Arabic numbers in parentheses. The reference styles for different types of publications are presented in the following examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The DSM V undoubtedly underestimate the prevalence of actual trauma in the general population, because it does not identify events that aren't life-threatening, for example, excessive emotional abuse, significant loss or separation, humiliation or humiliation, sexual experience with compulsion (not physical violence) as trauma. In addition, the criteria for post-traumatic stress disorder (Brewin & Holmes, 2003) and the diagnosis of acute stress disorder (Horowitz, Wilner, & Alvarez, 1979) are prerequisites, some people who suffer from significant post-traumatic stress are less likely to be diagnosed with stress disorder (Baysak, 2010;Briere & Scott, 2016;Cohen & Murch, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSM V undoubtedly underestimate the prevalence of actual trauma in the general population, because it does not identify events that aren't life-threatening, for example, excessive emotional abuse, significant loss or separation, humiliation or humiliation, sexual experience with compulsion (not physical violence) as trauma. In addition, the criteria for post-traumatic stress disorder (Brewin & Holmes, 2003) and the diagnosis of acute stress disorder (Horowitz, Wilner, & Alvarez, 1979) are prerequisites, some people who suffer from significant post-traumatic stress are less likely to be diagnosed with stress disorder (Baysak, 2010;Briere & Scott, 2016;Cohen & Murch, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most frequent traumatic events they face include encountering people exposed to man-made attacks, such as child deaths, social disasters, rape and torture, seeing a dead body or body part, removing the fragmented limbs or corpses from the crash site. It is also easier for healthcare personnel, who witness traumatic incidents while they response to such problems, that they experience problems such as acute stress disorder, posttraumatic stress disorder, major depression, psychosomatic disorders and substance use disorder (Baysak, 2010;Erkaya, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in cerebral perfusion pressure has an obvious effect on the Doppler waveform, with typical changes that include a decreased diastolic blood ow velocity [16]. When cerebral circulation stops, and intracranial pressure starts to increase for whatever reason, there is a decrease in end-diastolic blood ow velocity on TCD [24]. A modest increase in VD as opposed to VS was associated with complete recanalization/reperfusion, early neurological improvement, and a favorable functional outcome, suggesting that augmentation of diastolic ow may represent a novel therapeutic reperfusion target [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are many inconveniences in clinical application, which limit these methods as routine examination methods. Electroencephalogram (EEG) can continuously monitor patients with craniocerebral injury, but EEG detection is based on EEG resting as the diagnostic criteria of brain death, and there are still many problems in EEG resting as the diagnostic criteria, which has been controversial in clinical practice ( Kasapoglu et al, 2019 ). In recent years, some scholars have found that not all patients with clinical brain death have EEG resting state, but some patients have extensive EEG activities.…”
Section: Discussionmentioning
confidence: 99%